Microsaccades during high speed continuous visual search - Jacob G. Martin; Charles E. Davis; Maximilian Riesenhuber; Simon J. Thorpe (Journal of Eye Movement Research)
Here, we provide an analysis of the microsaccades that occurred during continuous visual search and targeting of small faces that we pasted either into cluttered background photos or into a simple gray background.  Subjects continuously used their eyes to target singular 3-degree upright or inverted faces in changing scenes.  As soon as the participant’s gaze reached the target face, a new face was displayed in a different and random location.  Regardless of the experimental context (e.g. background scene, no background scene), or target eccentricity (from 4 to 20 degrees of visual angle), we found that the microsaccade rate dropped to near zero levels within only 12 milliseconds after stimulus onset.  There were almost never any microsaccades after stimulus onset and before the first saccade to the face.  One subject completed 118 consecutive trials without a single microsaccade.  However, in about 20% of the trials, there was a single microsaccade that occurred almost immediately after the preceding saccade’s offset.  These microsaccades were task oriented because their facial landmark targeting distributions matched those of saccades within both the upright and inverted face conditions.  Our findings show that a single feedforward pass through the visual hierarchy for each stimulus is likely all that is needed to effectuate prolonged continuous visual search.  In addition, we provide evidence that microsaccades can serve perceptual functions like correcting saccades or effectuating task-oriented goals during continuous visual search.